PENGARUH KREDIBILITAS KONTEN DAN INTERAKSI MEDIA DI INSTAGRAM @KOPICALF TERHADAP MINAT BELI KONSUMEN - Mariska Salsabila Azzahra; Sari Ekowati (Tamilis Synex: Multidimensional Collaboration, 2026)
Instagram is a social media platform frequently utilized as a digital marketing tool due to its ability to facilitate consumer communication and interaction. The credibility of the content presented, combined with positive social media interaction, can enhance consumer interest in advertised products. This study aims to understand the impact of content credibility and social media interaction on consumer purchase intention regarding the @kopicalf Instagram account. The research employs a quantitative approach with an associative design. Purposive sampling was used to collect data from 100 respondents, and SPSS version 29 for Windows was utilized for analysis. The results indicate that Content Credibility (X₁) and Social Media Interaction (X₂) have a positive and significant influence on Consumer Purchase Intention (Y). This is evidenced by the partial test, where Social Media Interaction yielded a calculated t-value of 7.974 (exceeding the t-table value of 1.985) with a significance level of 0.021 (below 0.05); consequently, H₀ was rejected and Hₐ was accepted. Furthermore, the two independent variables simultaneously exerted a significant influence on Consumer Purchase Intention regarding the @kopicalf Instagram account.